Methodology of Islamic economics: overview of present state and future direction - Haneef, Mohamed Aslam; Furqani, Hafas (International Islamic University Malaysia, 2011)

(untitled)
This paper argues that research and publications in the area of methodology of Islamic economics is very significant for a meaningful development of the discipline. Although the discussion on methodology of Islamic economics in contemporary Islamic economics literature is rather limited, this paper reviews the works of selected scholars who have attempted to present works on ‘methodology’ and their approach to the process of theory building in Islamic economics. The paper then presents some implications of these views based on the position that methodology investigates the criteria, rationalizations, arguments and justifications used in theory appraisal as well as evaluating the reliability of theories, this paper concludes that greater resources, both human and financial, need to be channeled to developing uÎūl al-iqtiÎād, a fundamental, but vastly, neglected area of research in contemporary Islamic economics. JEL Classification: B41, B49, B59, Z12 Key words: Methodology, Islamic economics, uÎūl al-iqtiÎād.